Life cycle assessment of CRT lead recovery process. (1st December 2014) - Compagno, Lucio; Ingrao, Carlo; Latora, Antonio Giuseppe; Trapani, Natalia
In recent years, the high rate of technological obsolescence and subsequent replacement of ICT devices has led to a significant increase in waste from electrical and electronic equipment (WEEE) and oriented institutional stakeholders to promote recycling and material recovery to prevent the dispersion of hazardous substances into the environment and wastage of valuable resources. For cathode ray tube (CRT) WEEE, the standard treatment of end-of-life CRTs generates leaded glass which is usually landfill-disposed after inertisation. An experimental treatment was designed and applied to a pilot plant to obtain valuable secondary raw materials (SRMs). The industrialisation phase of the treatment requires assessing its sustainability according to the life cycle assessment approach. The paper analyses this treatment and from the significant results suggests it is environmentally sustainable.